Uji Penentuan Status Mutu Air Sungai Ayung Menggunakan Metode Storet - Ni Luh Widyasari; I Kadek Ardi Putra (Jurnal Ecocentrism, 2022)
Important role of rivers in daily life is used as a means of providing clean water, irrigation systems for farmers, transportation facilities and sports such as rafting. In Bali, rivers have an important role as a means of tourism activity. Utilization of water resources such as rivers in various activities will certainly affect the quantity and quality of rivers. The water quality of the Ayung River has decreased due to dense number of settlements around the river and heterogeneous community activity patterns with increased domestic waste production. Based on results from analysis parameter and determining status of river, it was found that Ayung River in the upstream, middle and downstream part was included in the lightly polluted category. This is due to the TSS and Faecal coliform parameters whose values ​​exceed the quality standard. Faecal coliform content upstream of the Ayung River is 170 MPN/100mL. The content of TSS and Faecal coliform in the middle of the Ayung River was 131 mg/mL and 84 MPN/100mL. Meanwhile, the content of TSS and Faecal coliform downstream of the Ayung River was 114 mg/mL and 790 MPN/100mL.